2010
DOI: 10.1039/b921810f
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane distribution of kanamycin and chloramphenicol: insights into the cytotoxicity of antibacterial drugs

Abstract: Antibiotics are widely used and their abuse has caused ecological hazard. Recently, pollution from pharmaceuticals and personal care products (PPCPs) has aroused great concern among governments and researchers. In order to elucidate the correlations among molecular structure, transmembrane distribution and toxicological effects of different kinds of antibiotics, zebrafish (Danio rerio) embryos and larvae were exposed to two structurally different antibiotics, kanamycin (KAN) and chloramphenicol (CAP). The memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…14,38,77,79 Pericardial oedema induced by glycyrrhizin has also been reported in a human adult. 80 Other literatures are consistent with the compound-specific malformation reported here (Fig.…”
Section: Compound Classmentioning
confidence: 99%
“…14,38,77,79 Pericardial oedema induced by glycyrrhizin has also been reported in a human adult. 80 Other literatures are consistent with the compound-specific malformation reported here (Fig.…”
Section: Compound Classmentioning
confidence: 99%
“…The early life stage (ELS) test using zebrafish embryos has been widely used to investigate the acute and chronic toxicity of chemicals that cause significant environmental and human health risks [41][42][43]. Furthermore, as the zebrafish shares many morphological and physiological characteristics with mammals, toxicological results from studies of zebrafish embryo development can be used to evaluate developmental toxicity in higher vertebrates [44,45]. Therefore, zebrafish embryos are an ideal model for studying vertebrate developmental toxicity, and the ELS test has become an effective method for testing adult fish.…”
Section: Introductionmentioning
confidence: 99%
“…The amount associated with the embryo decreased when NaCl exceeded 0.15 M. Increased ionic strength often favors hydrophobic interactions, thus facilitating the association of diclofenac with the embryo, while a higher concentration of electrolyte weakens embryo activity and thus affects the binding of diclofenac28. Higher temperatures favored the association of diclofenac with the embryo because an increase of the membrane flow rate accelerated metabolic activity28. However, more than 40°C could affect embryo activity adversely, so the amount of diclofenac associated was slightly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that, like other hydrophobic drugs in transmembrane transport studies, e.g. chloramphenicol, most of the drug remained in the extracellular solution28. However, only half of the diclofenac associated the membrane was transported into the cytoplasm, compared to over 80% of the adsorbed chloramphenicol28.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation